2018
DOI: 10.3389/fnins.2018.00668
|View full text |Cite
|
Sign up to set email alerts
|

CuII(atsm) Attenuates Neuroinflammation

Abstract: Background: Neuroinflammation and biometal dyshomeostasis are key pathological features of several neurodegenerative diseases, including Alzheimer’s disease (AD). Inflammation and biometals are linked at the molecular level through regulation of metal buffering proteins such as the metallothioneins. Even though the molecular connections between metals and inflammation have been demonstrated, little information exists on the effect of copper modulation on brain inflammation.Methods: We demonstrate the immunomod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 97 publications
4
42
0
Order By: Relevance
“…We have previously shown that the LPS treatment of primary astrocytes increases the secretion of IL6 and MCP-1. ( 29 ) The elevated levels of these cytokines have also been measured from AD patients. ( 30 , 31 ) The effect of LPS and AD transgenes on Lat1 mRNA expression was investigated by qRT PCR and protein expression was investigated by quantitative LC-MS/MS based proteomics.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown that the LPS treatment of primary astrocytes increases the secretion of IL6 and MCP-1. ( 29 ) The elevated levels of these cytokines have also been measured from AD patients. ( 30 , 31 ) The effect of LPS and AD transgenes on Lat1 mRNA expression was investigated by qRT PCR and protein expression was investigated by quantitative LC-MS/MS based proteomics.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, there is evidence that the immunomodulatory potential of systemic copper bis(thiosemicarbazones), which are stable, lipophilic neutral Cu 2+ complexes that are capable of crossing cell membranes and the blood-brain barrier. This compound can inhibit microglial and astrocytic activation, and reducing the acute cerebrovascular inflammation caused by bacterial lipopolysaccharide [130] . Based on the evidence above, it would be expected that increasing copper levels in the body would restore its homeostasis in the brain.…”
Section: Copper (Cu)mentioning
confidence: 99%
“…There is proof of the bis(thiosemicarbazone) copper(II) complex having the immunomodulatory potential [ 276 , 277 ], and greater BBB permeability. It inhibits microglial as well as astrocytic inflammatory responses and also has a role in the decrement of bacterial lipopolysaccharide (LPS) induced inflammation [ 278 ]. Some researchers have suggested that excess dietary Cu intake increases AD risks, and diets with measured copper should be supported.…”
Section: Therapeutics To Tackle Copper Ions In Admentioning
confidence: 99%